Development Of Test Data Navigator Tool (TDN) - Perumal, Usha Nantini (2016)
This project, titled "Development Test Data Navigator Tool (TDN)", aims to employ a solid tool strategy, which can deliver time savings and, eventually, cost savings by almost getting rid of the manual activity involved in determining, transforming, setting up, and maintaining test data sets. The Test Data Navigator Tool (TDN) is a mechanism for tracking the records of Standard Test Data Format (STDF) log files as well as CAMSTAR test summaries, and determining the aberrations of the records and the availability of data. The TDN is formulated using Microsoft Visual Studio and the Visual Basic (vb.net) programming language. The system essentially has two kinds of modules which aid in mining a test data location by means of the file transfer process logging: search record module, and export and save module. The TDN tool emphasises on addressing two critical issues in case involvement of additional resources and the average time for resolving a missing test data or summary problem. Through this mechanism, the procedure of tracking the record of a single lot or multiple lots becomes quite easier, facilitated by the click of a mouse. This tool offers user-friendly data entry with features such as a list box, checkbox and dropdown button menu for making the entry of inputs simpler to comprehend and use. The project has three objectives: (i) To study and scrutinise the gaps in the present data searching approach utilising time study; (ii) To introduce and formulate a fresh framework for enhancing the present data searching approach; (iii) To carry out a usability study and substantiate the formulated framework. For accomplishing the first objective, time study and brainstorming have been employed. A feasibility study was then carried out pertaining to TDN development concepts such as project theory, fact-finding, and old system study analysis as well as literature review to formulate a fresh framework. Lastly, a tool assessment was carried out after the framework was completed.